The effect of using group investigation learning model and prior knowledge toward student problem solving skills on Mathematics subject at junior high school - Angriani, V; Darto; Zein, M (Journal of physics. Conference series, 2021)
Towards the 21st century, technological and social change has developed rapidly. Educational practices must develop as well over time. The role and function of mathematics becomes an inevitable need. In order to meet the needs in adapting to these changes, problem solving is one of the mandatory skills that must be mastered by students. Problem solving skills are influenced by several factors, including learning models and student abilities. Therefore, this article aims at investigating whether a difference in mathematical problem solving skills emerges between the students involved in the learning group investigation learning model and those in the direct learning model, according to the high, medium, and low initial skills of 8th grade students of a junior high school (SMP) in Pekanbaru. The quasi-experimental method was used in the study. Based on the t-test analysis, the use of group investigation learning model in terms of initial skills, in general, influences the students’ mathematical problem solving skills.